Ultrasound Induces Aging in Granular Materials - Melo-Hurtado, F; Galaz-Donoso, B (2012)
Aging and rejuvenation have been identified as the general mechanisms that rule the time evolution of granular materials subjected to some external confinement pressure. In creep experiments performed in a triaxial configuration, we obtained evidence that relatively high intensity ultrasound waves propagating through the material induce both weakening and significant plasticity. In the framework of glassy materials, it is shown that the effect of ultrasound can be simply accounted for by a general variable, the fluidity, whose dynamics are described by an effective aging parameter that strongly decreases with sound amplitude and vanishes at the yield stress limit. The response from step perturbations in ultrasound intensity provided a method to assess the effective-viscosity jumps which are direct evidence of acoustic fluidization. © 2012 American Physical Society.